CH3OH/NH3 Mixture: A Possible Green Energy - Ruiz Gutiérrez, Adrián; Alzueta Ania, María Uxue; de Diego Escribano, Irene (Jornada de Jóvenes Investigadores del I3A, 2024)
Given the current problems with conventional fossil fuels, the study of the oxidation of more environmentally friendly fuels is on the rise. The oxidation of ammonia combined with oxygenated organic compounds could be a viable solution in the future to replace the most polluting fuels.